Studies on the hatching, growth and energy metabolism of ostrich chicks : Struthio Camelus var. Domesticus - Swart, Derick (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD(Agric) Animal Sciences))--University of Stellenbosch, 1988.